Lumbar alterations in magnetic resonance: correlation between Modic and Pfirrmann classifications - Rodrigues,Luciano Miller Reis (2014)
OBJECTIVE: To evaluate the relationship of sex and age with Modic and Pfirrmann classifications and verify the relationship between the two classifications in the group of patients studied. METHODS: 300 magnetic resonance scans (MRI) of the lumbar segment of the patients were evaluated; each lumbar segment (L1-L2, L2-L3, L3-L4, L4-L5 and L5-S1) was assessed according to Modic and Pfirrmann classifications. RESULTS: The type III of Pfirrmann was the most prevalent, whereas Modic was absent on most levels analyzed. The Modic signal was present mainly in the lower levels (L4-L5 and L5-S1) and in females. CONCLUSION: There is a strong correlation between the changes of the endplate and intervertebral discs, evidenced by changes in MRI. The relationship between Pfirrmann and Modic classifications is statistically higher the greater the disc degeneration.